The moderating role of social support on the impact of adverse childhood experiences on life satisfaction and mental health in adulthood - Muath Aldomini; Jerry W. Lee; Anna Nelson; Rhonda Spencer Hwang; Khulud K. Alharbi; Tassnym H. Sinky; Baraa S. Quronfulah; Wahaj A. Khan; Mohamed O. Elamin; Mohamed O. Nour (Clinical Epidemiology and Global Health)
Objectives: To evaluate the role of positive and negative social supports (PSS and NSS) in moderating the association of adverse childhood experiences (ACEs) with life satisfaction and mental health. Methods: A retrospective database analysis was done for the Biopsychosocial Religion and Health Cohort Study subjects (N = 10,194) residing in the United States and Canada (2006–2007). After controlling for confounders, a generalized linear model was used to evaluate the relationship between ACEs and life satisfaction and mental health, as well as the role of PSS subdomains (emotional, instrumental, informational, and companionship) and NSS subdomains (rejection or neglect, unsympathetic behavior, unwanted advice, and failure to provide help) had in these relationships. Result: The study sample was mainly composed of females (67.5 %) and Whites (63.6 %) with an average age of 61.65 ± 13.59 years old. About 60.6 % of participants reported experiencing at least one ACE. ACEs have a negative association with life satisfaction and mental health. Better mental health and life satisfaction were favorably associated with PSS and negatively associated with NSS, respectively. With the exception of the rejection subdomain, NSS had no deteriorating influence on the relationship between ACEs and poor mental health and life satisfaction. In contrast, PSS significantly mitigated this relationship. Conclusions: When predicting both mental health and life satisfaction following ACEs, potential protective effects of PSS (mainly instrumental support) and debilitating effects of NSS (rejection) were noted. When interacting with individuals who have had ACEs, health providers need to be mindful of the possible effects of both PSS and NSS. More long-term studies are necessary, particularly in more diverse groups.